Effects of synbiotic dietary supplementation with quorum quenching properties on macrobrachium rosenbergii de man juveniles - Wee, Wen Chen (2016)
Dietary supplementation of functional feed additives such as probiotics, prebiotics and synbiotic are widely studied in aquaculture to potentially enhance the growth of aquatic animals. Many pathogenic Gram-negative bacteria in fish and shrimp have been reported to use quorum sensing (QS) signal molecules to induce the production of virulence factors. The aim of this study was to examine the effects of probiotic, prebiotic and synbiotic on the growth and health performance in Macrobrachium rosenbergii. The first study was to isolate QS degrader from the prawn with prebiotic utilization activity. Two QS degrader strains, BP-MBRG/1b and BP-MBRH/1b were isolated from the gut and hepatopancreas of adult Macrobrachium rosenbergii. Isolation of QS degraders was based on the ability of microbial community to grow in a minimal medium which contains only the mixture of N-Acyl homoserine lactones (AHL). The QS degrader strain isolated from the gut showed strong inhibition of AHL and was identified as Bacillus cereus (BP-MBRG/1b). The results also showed that the degrader strain BP-MBRG/1b grew well in fructooligosaccharide (FOS) agar medium. Later, the second study was designed to investigate the effects of dietary prebiotic FOS at 0.1%, 0.4%, 1% and 2% to determine the optimum inclusion level of FOS required by M. rosenbergii post-larvae (PL) after 56 days of feeding. The specific growth rate (SGR) was significant (p < 0.05) highest in the 0.4% FOS fed PL. Furthermore, 0.4% FOS also significantly (p < 0.05) stimulated the highest intestinal short-chain fatty acids (SCFAs) production compared to the control treatment. After 56 days, the hepatopancreatic tubules of prawns in the 0.4% FOS treatment were more closely arranged with significantly (p < 0.05) more R- and E-cells. However, oxidative stress in prawns was increased with the increased of FOS concentration. Lastly, the third experiment was conducted to evaluate the effects of the probiotic and FOS in single or combined diets (synbiotic) supplementation in M. rosenbergii juveniles. After 28 days of feeding, results showed that the SGR was significant (p < 0.05) highest in the prawns fed with probiotic diet, accompanied by increased superoxide dismutase activity (SOD) and SCFAs. The prawns were then challenged with pathogenic Aeromonas hydrophila AH-1N via static immersion. Prebiotic fed prawns had the highest survival although survival response was not significant (p > 0.05) different among the treatment. Both prebiotic and synbiotic diet significantly (p < 0.05) enhanced the SOD in prawns, suggesting the induction of reactive oxygen species (ROS) in order to kill pathogenic bacteria. Histological observations of hepatopancreas showed differences in severity and type of cell/tissue damage where synbiotic fed prawns showed the best hepatopancreas condition. In addition, synbiotic showed the greatest protection effects in juvenile prawns when A. hydrophila was present. Overall, this study showed that dietary FOS stimulated the growth in PL while probiotic diet enhanced the growth in juvenile prawns. In conclusion, dietary prebiotic supplementation stimulated the growth in PL while probiotic diet enhanced the growth in juvenile prawns. Synbiotic diet showed potential in protecting the prawn from A. hydrophila based on histological observation. The outcome of this study suggested addition of feed additives probiotic, prebiotic and synbiotic exert different beneficial effects in the prawns. Further optimization and study of additives inclusion dosage in diets are required as the present study showed probiotic, prebiotic and synbiotic exert different positive effects in M. rosenbergii.